(untitled) (Dhaka University Journal of Biological Sciences, 2015)
Effects of four different feeds on growth and nutrient composition of mrigal fingerlings (Cirrhinus mrigala) were evaluated. After 30 days of rearing growth parameters and quality of fish flesh were examined. During the rearing period, the change in growth and feed utilization by the mrigal fed with feeds have been assessed as condition factor (K), average daily gain (ADG), specific growth rate (SGR) and feed conversion ratio (FCR).The highest FCR (6.23 ± 0.59) was found in the treatment 4 while the lowest (3.08 ± 0.10) in the treatment 1. The condition factor was highest (0.89 ± 0.01) in treatment 1 while the lowest (0.81 ± 0.05) in the treatment 4. After 30 days of rearing, moisture content of mrigal in different treatments was 77.2, 78.41, 76.99 and 77.86% in treatments 1, 2, 3 and 4, respectively. Protein was 17.15, 15.89, 16.90 and 14.76% in treatments 1, 2, 3 and 4, respectively. Lipid was 2.07, 2.22, 2.25 and 2.85% and ash content was 3.58, 3.48, 3.88 and 4.53% in four (1, 2, 3 and 4) treatments, respectively. Dhaka Univ. J. Biol. Sci. 24(2): 153-159, 2015 (July)